1986
DOI: 10.2307/1130373
|View full text |Cite
|
Sign up to set email alerts
|

Automaticity, Retrieval Processes, and Reading: A Longitudinal Study in Average and Impaired Readers

Abstract: In this longitudinal investigation, the development of word-retrieval speed and its relationship to reading was studied in 72 average and 11 severely impaired readers in the kindergarten to grade 2 period (5-8 years). Subjects received a battery of 3 reading measures and 4 continuous naming tests with varied stimulus requirements. Results indicated that the relationship of retrieval speed to reading is a function of development and the correspondence between higher- and lower-level processes in the specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
248
3
15

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(280 citation statements)
references
References 0 publications
14
248
3
15
Order By: Relevance
“…Finally, although the deficit groups hypothesized by Wolf andBowers (1999, 2000) were identifiable, these groups did not display the expected characteristics hypothesized by the double-deficit model. Although RAN tasks have been shown to have predictive ability in the early school years (Torgesen et al, 1997;Wolf et al, 1986), this predictive ability seems to lessen with time (Torgesen et al, 1997), and, in the present study, did not provide additional information about comprehension ability over and above reading rate and vocabulary. The results of the present study suggest that measures of phonological processing and naming speed may be useful in identifying adults with RD, although the inclusion of measures of naming speed does not provide additional diagnostic information independently of reading rate and vocabulary.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Finally, although the deficit groups hypothesized by Wolf andBowers (1999, 2000) were identifiable, these groups did not display the expected characteristics hypothesized by the double-deficit model. Although RAN tasks have been shown to have predictive ability in the early school years (Torgesen et al, 1997;Wolf et al, 1986), this predictive ability seems to lessen with time (Torgesen et al, 1997), and, in the present study, did not provide additional information about comprehension ability over and above reading rate and vocabulary. The results of the present study suggest that measures of phonological processing and naming speed may be useful in identifying adults with RD, although the inclusion of measures of naming speed does not provide additional diagnostic information independently of reading rate and vocabulary.…”
Section: Discussioncontrasting
confidence: 81%
“…That naming speed was found to be more important to reading comprehension than vocabulary and phonological processing is consistent with the double-deficit hypothesis. However, this finding is inconsistent with previous naming speed research, which has found that naming speed is not related to reading comprehension (e.g., Bowers & Swanson, 1991;Meyer et al, 1998b;Pennington et al, 2001;Schatschneider et al, 2002;Wolf et al, 1986). The role of naming speed in comprehension should be investigated further.…”
Section: Discussioncontrasting
confidence: 73%
“…Wolf, Bally, and Morris (1986) found that within a group of 83 Grade 2 children followed since kindergarten, RAN lost its predictive power by Grade 2. They concluded that as RAN ability becomes more automatic, it differentiates children with dyslexia from typical readers but does not have predictive power.…”
Section: The Nature Of the Relationship Between Naming Speed And Readmentioning
confidence: 99%
“…Moreover, PA skills do not appear to differ between children who evidence a discrepancy between IQ and reading and nondiscrepant poor readers (e.g., Fletcher et al, 1994;Stanovich & Siegel, 1994). The relation of VNS with reading is strong in all young readers, although there is typically a maximal (ceiling) performance by the end of the second grade for average (but not impaired) readers (Wolf, Bally, & Morris, 1986). There has been some debate regarding the specific versus general nature of timing deficits, with some studies (e.g., Kail & Hall, 1994) finding that VNS was related to decoding skills through the mediation of general cognitive processing speed.…”
mentioning
confidence: 89%